2006
DOI: 10.1097/01.bpb.0000194439.75378.ac
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of a congenital pseudarthrosis of the tibia by osteogenic protein-1 (bone morphogenetic protein-7): a case report

Abstract: Congenital pseudarthrosis of the tibia remains one of the most difficult orthopaedic problems to treat. Before the use of a recombinant bone morphogenetic protein (bone morphogenetic protein-7; osteogenic protein-1) the patient with congenital pseudarthrosis of the tibia in this report had had 12 unsuccessful surgeries. Five months after radical resection of sclerotic tibial segments, Ilizarov fixation and administration of osteogenic protein-1 osteogenic device, the congenital pseudarthrosis of the tibia heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 3 publications
1
24
0
1
Order By: Relevance
“…However, the reported results are contradictory. In two case reports, successful osteosynthesis was achieved 23,24 , but in a case series of five patients with congenital pseudarthrosis of the tibia who were treated with rhBMP-7 and intramedullary rods or external fixation, unequivocal union was achieved only in one patient 25 . The in vitro data obtained during the present study suggest that BMP treatment may not induce fibrous hamartoma cells to differentiate to osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…However, the reported results are contradictory. In two case reports, successful osteosynthesis was achieved 23,24 , but in a case series of five patients with congenital pseudarthrosis of the tibia who were treated with rhBMP-7 and intramedullary rods or external fixation, unequivocal union was achieved only in one patient 25 . The in vitro data obtained during the present study suggest that BMP treatment may not induce fibrous hamartoma cells to differentiate to osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…There are over 30 of them, but only two have been developed for application in mankind and produced by genetic engineering: the recombining BMP2 and BMP7. The use of rhBMP in pseudarthrosis of the tibia seems promising in the light of initial observations published about children [12][13][14][15][16][17][18]45] and the results obtained in adults [1,2]. In children, the question arises as to the early and long-term side effects.…”
Section: Application Of Bmpmentioning
confidence: 99%
“…The results obtained using BMPs in adults, particularly in the case of pseudarthrosis of long bones, have opened up the perspective of applying these proteins to children in certain highly complex situations. A few authors have reported their experience in compassionate indications, especially CPT [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the United States, OP-1 has been approved in 28 other countries, including Canada, Australia, and the European Union [27]. Although contraindicated in children, BMPs have been used off-label in some difficult nonunions in children [2,7,11,20,23]. In these cases, the benefits of using BMPs may outweigh the abovementioned concerns.…”
Section: Introductionmentioning
confidence: 99%